Pengaruh Fintech terhadap Pertumbuhan Kredit Perbankan dan Pertumbuhan Ekonomi - Immi Fiska Tarigan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Technological development also leads to financial services which are called financial technology. Its use has a positive impact on making it easier to borrow money and improving the welfare and economy of the community. The aim of this research is to determine the influence that fintech services have on credit and economic growth and to determine the relationship between each of these variables. This research is quantitative by utilizing linear regression to process the research data being developed. The result was that credit was able to grow, influenced by fintech, which was due to the ease of accessing and obtaining it without heavy conditions like conventional banks and through fintech, the general public throughout Indonesia was able to feel the impact of economic growth. Overall the results have a positive effect. Meanwhile, the relationships generated by fintech are quite strong in influencing credit and economic growth.